1994
DOI: 10.3733/ca.v048n02p35
|View full text |Cite
|
Sign up to set email alerts
|

Predatory beetle may suppress silverleaf whitefly

Abstract: try. Yet, with the possible exception of the commercially available wasp Encarsia forrnosa Gahan, their ability to suppress B. tabaci populations under a variety of conditions has not been determined. Here we report our findings on Delphastus pusillus (LeConte), one of the several natural enemies we are evaluating for use in B. tabaci biologi-E cal control programs in field crops and greenhouse-grown poinsettias. I3 1: 7 Small, shiny beetle I Adult Delphastus pusillus feeding on a Bemisia tabaci nymph. A third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Booth and Polaszek [63] based their comments about the species on additional laboratory material from Israel and the Netherlands (cultures from Israel) and the U.K. (cultures from Canada). In addition, a similar species, D. pusillus, was released in several augmentative biological program attempts [67,68]. However, because our results demonstrated that the species considered D. pusillus reared in commercial insectaries was instead D. catalinae, only the latter was probably to date used in biological control programs [63,69].…”
Section: Discussionmentioning
confidence: 98%
“…Booth and Polaszek [63] based their comments about the species on additional laboratory material from Israel and the Netherlands (cultures from Israel) and the U.K. (cultures from Canada). In addition, a similar species, D. pusillus, was released in several augmentative biological program attempts [67,68]. However, because our results demonstrated that the species considered D. pusillus reared in commercial insectaries was instead D. catalinae, only the latter was probably to date used in biological control programs [63,69].…”
Section: Discussionmentioning
confidence: 98%
“…A scientific approach to analyze the competitive effects of natural enemies is beneficial to the study of the coexistence of multiple natural enemies and the selection of the most efficient natural enemy combination for efficient control of pests without damaging the original ecological environment of tea plantations. The results of cage experiments in American cotton fields show that the combination of multiple natural enemies in biological control is more effective than using one natural enemy alone (Heinz et al 1994). In this article, several natural enemies with high competitiveness are the first natural enemies to be protected and utilized in the biological control practice of E. onukii .…”
Section: Discussionmentioning
confidence: 99%
“…Average whitefly oviposition rates and tomato leaf trichome densities were 6.4 (SEM = 0.73, N = 50 females) ovipositions per day and 388.5 (SEM = 33.94, N = 115 leaves) trichomes per 25 mm 2 of leaf tissue for the cultivar Alta, and 3.3 (SEM = 0.51, N = 50 females) ovipositions per day and 125.2 (SEM = 10.26, N = 124 leaves) trichomes for the cultivar VF145B7879) (Heinz & Zalom, 1995). Delphastus pusillus was selected as the test animal because it has previously been shown to significantly reduce Bemisia populations in laboratory (Hoelmer et al, 1993), greenhouse (Heinz & Parrella, 1994a), and field (Heinz et al, 1994) studies. Results from these life history studies were followed by population studies in greenhouses to test whether variation in trichome densities and D. pusillus life history characteristics yielded cultivar-specific differences in whitefly population growth and whitefly population suppression by D. pusillus.…”
Section: Methodsmentioning
confidence: 99%
“…Although biological control is often espoused as an alternative to chemical control, it presently has only been effective in managing B. argentifolii infesting selected greenhouse crops (Breene et al, 1992;Heinz & Parrella, 1994a;McMahon et al, 1994). Biological control of Bemisia infesting field crops has been largely unsuccessful (Anonymous, 1981;Dittrich et al, 1985;Meyerdirk et al, 1986;Dowell, 1990), presumably due to epis-odes of mass migrations of whitefly that overwhelm the natural enemy complex (Heinz et al, 1994;Simmons & Minkenberg, 1994). Plant cultivars that may slow Bemisia population growth have been identified (Mound, 1965;Butler & Henneberry, 1984;Berlinger, 1986;Ozgur & Sekeroglu, 1986;Heinz & Zalom, 1995), but cultivars truly resistant to whitefly oviposition are not yet commercially available.…”
Section: Introductionmentioning
confidence: 99%